Pretend Play and Project-Based Learning as Factors in the Development of Preschool Children - Nikolay E. Veraksa; Aleksandr N. Veraksa; Valeria A. Plotnikova (Peoples' Friendship University of Russia (RUDN University), 2023)
In psychology, playing is traditionally considered the most developing form of preschool children's activity. Nowadays, despite the large amount of research demonstrating the significant impact of pretend play on the psychological development of the preschoolers, project-based learning is widespread in kindergartens. Therefore, the purpose of this work is to determine whether it is enough for the successful development of the preschool children to include them in pretend play or whether it is important to use other educational technologies as well. According to the cultural-historical and activity-based approaches in the educational psychology, the key features of play and project-based learning are identified as fundamental for the development of the preschoolers. Based on the identified key features, the authors conduct a comparative analysis of play and project-based learning in order to determine their fundamental differences. The results of the analysis show that these types of activities have their own developmental tools: an imaginary situation (in play) and a space for children's realization (for project-based activity). It is also demonstrated that inclusion in pretend play involves a process orientation caused by the underdevelopment of the operational sphere in the preschoolers, while project-based learning is result-oriented activity aimed at creating a socially significant product. Finally, an essential point in play and project-based activity is associated with the role of the adult. In play, the child is independent, being the subject of play activity. In project activities, the child is the author of an idea, with the adult being the child's interpreter. The research shows the fundamental differences between pretend play and project-based activity for the development of the preschoolers, which should be taken into account when working with children of this age.